2010
DOI: 10.1093/ndt/gfq675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic kidney disease on the expression of thiamin and folic acid transporters

Abstract: CKD results in marked down-regulation in the expression of folate and thiamin transporters in the intestine, heart, liver and brain. These events can lead to reduced intestinal absorption and impaired cellular homeostasis of these essential micronutrients despite their normal plasma levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…36 Further disturbance of thiamine metabolism in renal failure occurs by decreased expression of thiamine transporters in small intestine, heart, liver and brain and likely decreased availability of thiamine at these sites. 37 Herein we showed that incubation of red blood cells from HD patients ex vivo with thiamine restored normal levels of transketolase activity and R5P concentration, consistent with correction of impaired pentose pathway activity.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…36 Further disturbance of thiamine metabolism in renal failure occurs by decreased expression of thiamine transporters in small intestine, heart, liver and brain and likely decreased availability of thiamine at these sites. 37 Herein we showed that incubation of red blood cells from HD patients ex vivo with thiamine restored normal levels of transketolase activity and R5P concentration, consistent with correction of impaired pentose pathway activity.…”
supporting
confidence: 59%
“…Recent studies in diabetes and CKD suggest there are also abnormalities of thiamine transport due to tissue-specific down regulation of thiamine transporters. 14,37,47 Measurement of renal clearance of thiamine is a sensitive clinical marker of this. 14 Red blood cell transketolase activity is valuable to assess impact on the pentosephosphate pathway and αETKA to explore cause of transketolase activity deficit.…”
Section: In Clinical Translation Dietary Deficiency Of Thiamine -Leamentioning
confidence: 99%
“…These microvascular pathologies, such as thrombosis, are mediated by inflammatory, atherogenic, and oxidative mechanisms. 18,21 Furthermore, clinical changes observed in patients with CKD, such as low intracellular levels of folate and thiamine, 22 or aberrant nitric oxide metabolism, 23 can increase susceptibility to cerebral infarction and white matter hyper-intensities (lesions) in the brain ( Figure 1, Table 1). 21,23 Small vessel disease (SVD) is a pathological process that affects the arterioles, venules, and capillaries, causing ischaemic or haemorrhagic lesions.…”
Section: Microvascular Diseasementioning
confidence: 99%
“…Anorexia and insufficient dietary intake are regarded as the most important contributors [2,3]. However, new contributors have emerged recently, including impaired gastrointestinal absorption by specific transporters, or the role of microbiota in the production of thiamine antagonist, oxythiamine, both, importantly, influenced by ESRD [4,5]. …”
Section: Introductionmentioning
confidence: 99%